Her2+ and b-HCG Producing Undifferentiated Gastric Adenocarcinoma - Sahar Eivaz-Mohammadi; Fernando Gonzalez-Ibarra; Waheed Abdul; Omer Tarar; Khurram Malik; Amer K. Syed (Case Reports in Medicine)
A 25-year-old Hispanic female with a history of anemia, schizoaffective disorder, and psychosis was admitted for anemia associated with fatigue, weakness, shortness of breath, night sweats, weight loss, and abdominal and lower back pain for the past two months. On routine management, she was found to have a positive serum b-HCG of 80.4 (0–5 mIU/mL) but the patient denied any sexual activity in her life. During her admission, U/S of the pelvis was noncontributory. CT angiogram of the chest was significant for prominent mediastinal and hilar lymph nodes, diffusely thickened stomach suggesting gastric malignancy with multiple hypoenhancing lesions in the liver and diffuse lytic lesions in the spine and sacrum suspicious for metastatic disease. The MRI of the abdomen confirmed the CT angiogram findings. After these findings, EGD was performed which showed lesions in the antrum, body of the stomach, fundus, and cardia on the lesser curvature of the stomach body correlating with carcinoma. The biopsy was positive for Her2, b-HCG producing poorly differentiated gastric adenocarcinoma. Patient underwent one successful round of chemotherapy with Taxotene, Cisplatin, and 5-FU for Stage IV gastric adenocarcinoma.